Phenology of the production of flowers and fruits of wild and hybrid species of the genus Passiflora - Esashika,Danilo Akio de Sousa (2018)
Abstract Wild species of passion fruit have characteristics that could be used in the passiflora culture, among them the production of fruits in the off-season of the sour passion fruit. The objective of this work was to evaluate the phenology of flowers and fruits production in wild species cultivated in the Brazilian Savanna Central Region. For each access, a 1-meter-long strip (2 m2) was evaluated for the presence of flowers and fruits from January 2015 to December 2016. The hybrid and wild species of passiflora that produce floral buds, flowers and fruits during the off-season of passion fruit sour include: BRS Céu do Cerrado (P. incarnata x P. edulis), P. alata Dryand, P. bahiensis Klotzsch, P. coccinea Aubl., P. maliformis L., P. quadriglandulosa Rodschied, P. auriculataKunth, P. decaisneana G. Nicholson, P. sidifolia M. Roem., P. suberosa L., P. tholozanii Sacco, P. quadrangularis x P. alata. It was also verified the presence of species and hybrids with high ornamental potential due to the beauty of their flowers and their production during the whole year, such as: P. suberosa L., P. tholozanii Sacco, P. coccinea x P. setacea, P. coccinea x P. quadrifaria. These species and hybrids have high potential for passiflora breeding programs as a source of genes of interest.